2022
DOI: 10.1021/acsami.2c05488
|View full text |Cite
|
Sign up to set email alerts
|

Fast Charge Transfer and High Stability via Hybridization of Hygroscopic Cu-BTC Metal–Organic Framework Nanocrystals with a Light-Absorbing Layer for Perovskite Solar Cells

Abstract: Perovskite solar cells (PSCs) have great potential as an efficient solar energy harvesting system due to their outstanding optoelectronic properties, but the charge accumulation and recombination, as well as the moisture-induced degradation of the light-absorbing perovskite layers, remain great bottlenecks in practical applications for future technology. As a solution to this challenge, here we report a strategy to realize moisture-stable PSCs allowing fast charge transfer that, in turn, leads to high power co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…It was further confirmed that the modification of the buried interface by MACl@ZIF-8 accelerated the electron transfer. 4,56 To evaluate the trap density of the perovskite films on different ETLs, we performed space-charge limited current (SCLC) measurements by employing the electron-only structure of FTO/SnO 2 /perovskite/PCBM/Ag. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It was further confirmed that the modification of the buried interface by MACl@ZIF-8 accelerated the electron transfer. 4,56 To evaluate the trap density of the perovskite films on different ETLs, we performed space-charge limited current (SCLC) measurements by employing the electron-only structure of FTO/SnO 2 /perovskite/PCBM/Ag. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This result comes from a more efficient extration of photo‐generated carrier from the perovskite to the TiO 2 . [ 59 ] The TRPL spectra are fitted by the doubled‐exponential decay function f ( t ) = A 1 exp(− t / τ 1 ) + A 2 exp(− t / τ 2 ), where A 1 and A 2 are the decay amplitudes, and τ 1 and τ 2 are the decay time constants. [ 60 ] The fitted parameters are summarized in Table S2, Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…Small-sized CPMs. Small-size MOFs, typically with diameters less than 5 nm, can be obtained by adjusting the concentration of reactants 39 or by using ultrasound-assisted methods, [40][41][42] which is also the strategy adopted by most poorly soluble MOFs. Such small sizes being incorporated into the perovskite layer do not lead to an inhomogeneous multilayer structure.…”
Section: Low Solubility Cpmsmentioning
confidence: 99%